Carbon nanofibrous electrode material from electrospinning of chlorella (microalgae) with polyacrylonitrile for practical high‐performance supercapacitor. (23rd August 2022) - Hasan, Md Faruque; Mantripragada, Shobha; Gbewonyo, Spero; Xiu, Shuangning; Shahbazi, Abolghasem; Zhang, Lifeng
Summary: In recent years, carbon nanofibrous materials from electrospinning polyacrylonitrile (PAN) have been developed for freestanding electrode materials. However, there is still a large room to improve the electrochemical performance of this type of electrode material for supercapacitor purposes. In this research, an attempt is made to enhance the electrochemical performance of electrospun carbon nanofibrous material (ECNF) as an electrode for supercapacitor application by incorporating chlorella, a single‐celled green freshwater microalga that grows naturally worldwide, in combination with carbon activation. The chlorella was mixed with PAN up to an equal amount in spinning solution and electrospun to nanofibrous material followed by carbonization and further activation. The investigation of electrochemical performance of chlorella‐derived carbon nanofibrous electrode materials before and after activation (C‐ECNF and C‐ECNFa) indicated that chlorella is a superior natural resource as nitrogen (N) and phosphorus (P) dopant as well as mesopore promoter to develop practical high‐performance carbon nanofibrous electrode material for supercapacitor application. Abstract : Coupling activation with chlorella incorporation in electrospun carbon nanofibrous material can result in superior stand‐alone electrode material for supercapacitor use. Chlorella is found to be a superior natural resource as nitrogen (N) and phosphorus (P) dopant as well as mesopore promoter for the carbon nanofibrous materials. This research shed light on the efficient use of natural resources for carbon‐based electrode material in energy storage applications from an economic and environmental viewpoint.